A chatbot using Levenshtein distance algorithm for Raspberry board - Truong Ngoc Son; Vo Thanh Nhan; Le Minh; Le Minh Thanh; Nguyen Van Phuc; Dang Phuoc Hai Trang (Journal of Technical Education Science, 2020)
In this paper, we present a chatbot based on the Levenshtein Distance for low-cost embedded systems. The state-of-the art chatbots are based on deep neural networks, however, such chatbots cannot be deployed on the low-cost embedded system, such as Raspberry board for mobile robots. Chatbot based on Levenshtein Distance requires fewer resources and can be deployed on low-cost embedded systems efficiently. The Levenshtein distance represents the similarity between the two strings. The similarity between the input question and all the stored questions in the database are measured. A winner is a stored question that is the best similar to the input question. Having recognized the question, chatbot can decide the output by querying from the database. Chatbot using (a) search algorithm based on Levenshtein distance is faster by 15 times and 75 times than the Convolutional Neural Network and the LSTM network. The chatbot based on Levenshtein Distance is suitable to be deployed on the low-cost embedded systems for mobile robots.